Effect of Water-soluble Polysaccharides Plant Extraction of the Saussurea Genus on the Activity of Mice Peritoneal Macrophage NO-synthase - A. A. Ligacheva; E. I. Gulina; I. V. Shabanova; E. S. Trofimova; S. V. Krivoshchekov; N. V. Gurkin; M. N. Shurupova; E. Yu. Sherstoboev; M. G. Danilets; M. V. Belousov (Разработка и регистрация лекарственных средств)
Introduction. The nitric oxide molecule is one of the most versatile, multifunctional mediators of biological reactions in the body. NO participates in the formation of innate and specific immunity, the inflammatory process and protection against infectious pathogens. It is known that polysaccharides of higher plants are widely used to activate pro- and anti-inflammatory reactions. Previous studies have shown the promise of a more detailed research in the immunomodulatory properties of plant polysaccharides of the genus Saussurea DC, the mechanisms of their immunostimulating and anti-inflammatory action depending on the origin and conditions of extraction.Aim. The aim of present research was to evaluate the dependence of the affection of the extraction parameters of water-soluble polysaccharides (WSPS) from the aerial parts of S. salicifolia (L.) DC., S. controversa DС., S. frolovii Lebeb. on NO synthase activity and peritoneal macrophages proliferation.Materials and methods. Chemical methods for the isolation of water-soluble polysaccharides, cultural and biochemical methods for assessing biological activity were used.Results and discussion. Water-soluble polysaccharides (WSPS) from plants S. salicifolia (L.) DC., S. controversa DС., S. frolovii Ledeb. obtained with different extraction parameters have the ability to enhance production of nitrites antigen-presenting cells in the same way as standard macrophage activator liposaccharide. Polysaccharides from S. controversa and S. frolovii at acidic extractant are free of endotoxin impurities. All water-soluble polysaccharide samples obtained using neutral and alkaline extractants contain endotoxin impurities. Samples from the S. controversa contained this impurity after extraction in an acidic extractant. Polysaccharide samples are not cytotoxic.Conclusion. It was stated that water-soluble polysaccharides from plants of the Saussurea genus using an acidic extractant do not possess cytotoxic properties, do not contain endotoxin impurities and significantly enhance the production of nitric oxide by macrophages. These samples used in a detailed study of the immunomodulatory properties and further development on their basis of new treatment methods various diseases that require correction and regulation of the functional activity of immune cells, including macrophages.